2009
DOI: 10.1007/s10815-009-9370-2
|View full text |Cite
|
Sign up to set email alerts
|

Vitrification of mouse embryos at 2-cell, 4-cell and 8-cell stages by cryotop method

Abstract: Purpose The objective of this study was to investigate the effects of vitrification on the preimplantation developmental competence of mouse 2-cell, 4-cell and 8-cell stage embryos. Methods Mouse 2-cell, 4-cell and 8-cell stage embryos were cryopreserved using the cryotop vitrification method and subsequently warmed on a later date. The embryos were then assessed by their morphology, blastocyst formation and hatching rates. Additionally, trophectoderm (TE) and inner cell mass (ICM) cell numbers were compared i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 37 publications
(39 reference statements)
4
35
1
Order By: Relevance
“…Hatched blastocysts developed from vitrified zygotes by cryotube, and in-straw methods (Bagis et al, 2004(Bagis et al, , 2005 and from vitrified two-cell, four-cell, and eightcell embryos by cryotop method (Zhang et al, 2009b) did not show significant alteration in cell numbers in developed blastocysts.…”
Section: Biological Impacts Of Cryopreservation On Embryos Viability mentioning
confidence: 87%
See 1 more Smart Citation
“…Hatched blastocysts developed from vitrified zygotes by cryotube, and in-straw methods (Bagis et al, 2004(Bagis et al, , 2005 and from vitrified two-cell, four-cell, and eightcell embryos by cryotop method (Zhang et al, 2009b) did not show significant alteration in cell numbers in developed blastocysts.…”
Section: Biological Impacts Of Cryopreservation On Embryos Viability mentioning
confidence: 87%
“…Reciprocal studies on the effect of vitrification on the number of cells in blastocysts were conducted by Bagis et al (2004) and Zhang et al (2009b), independently. Hatched blastocysts developed from vitrified zygotes by cryotube, and in-straw methods (Bagis et al, 2004(Bagis et al, , 2005 and from vitrified two-cell, four-cell, and eightcell embryos by cryotop method (Zhang et al, 2009b) did not show significant alteration in cell numbers in developed blastocysts.…”
Section: Biological Impacts Of Cryopreservation On Embryos Viability mentioning
confidence: 99%
“…Several studies on mammalian embryos have proven that the best tool for vitrification is cryotop [28,[34][35][36]. In the Zhang study [36], the vitrified mouse embryos derived in vivo with cryotop showed survival rates of 96 % for two-cell vitrified embryos. Yan and coworkers [37] vitrified two-cell mouse embryos derived from IVF with OPS, and reported the survival rate of 51 %.…”
Section: Discussionmentioning
confidence: 98%
“…The vitrification of cleavage-stage embryos has also been tested [9][10][11]. At the present, a wide variety of protocols and procedures are available [12][13][14].…”
Section: Introductionmentioning
confidence: 99%